2010
DOI: 10.1002/ejoc.201000375
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics and Hydration Properties of Small Antifreeze‐Like Glycopeptides Containing Non‐Natural Amino Acids

Abstract: Novel studies on the synthesis and conformation in aqueous solution of three antifreeze‐like glycopeptides containing the sequence Xaa(α‐GalNAc)‐Ala‐Ala, with Xaa being threonine (Thr) or the non‐natural amino acids α‐methylserine (MeSer) or α‐methylthreonine (MeThr), are reported. The study has combined NMR experiments with molecular dynamics simulations. Whereas the Thr derivative is rather rigid in solution and exhibits an extended conformation for the backbone, the non‐natural glycopeptides are fairly flex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…[18][19][20][21] However, from a rational design viewpoint, it is mandatory that the novel derivatives retain the bioactive conforma- tion, being capable to serve as ligands for specific receptors. Our experience indicates that this unnatural a-methylserine, previously synthesized in our laboratory, 22 favours a helix-like conformation, [23][24][25][26][27] thus maintaining the key structural features required for the bioactivity.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…[18][19][20][21] However, from a rational design viewpoint, it is mandatory that the novel derivatives retain the bioactive conforma- tion, being capable to serve as ligands for specific receptors. Our experience indicates that this unnatural a-methylserine, previously synthesized in our laboratory, 22 favours a helix-like conformation, [23][24][25][26][27] thus maintaining the key structural features required for the bioactivity.…”
mentioning
confidence: 71%
“…Notably, although the synthesis of several biologically active peptides containing Ca-methylated amino acids has been described, 28,29 only some of them have been incorporated into glycopeptides. 23,26,27,30 Moreover, to the best of our knowledge, while the biological activity of some unnatural glycopeptides has been reported, 19,21 this particular type of glycopeptides containing Ca-methylated amino acids has not been tested yet in biological assays.…”
mentioning
confidence: 99%
“…Corzana and co-workers have conducted conformational analyses of short glycopeptides derived from MUC1. 30,[36][37][38] As a result of the extra flexibility displayed by the peptide motif in this kind of compounds, the NOE-derived distances and coupling constants are used with MD-tar. In stark contrast to classical constraints, this technique provides a distribution of low-energy conformers that can quantitatively reproduce the NMR spectroscopic data.…”
Section: Effect Of A-o-glycosylation On Peptide Backbone Conformationmentioning
confidence: 99%
“…It has been also found that in the glycosylated serine substituted glycopeptides that the acetamide groups assumed more apical positions with the peptide backbones distanced from the sugar, allowing more rotational freedom around the O-glycosidic bond. 34,35 Recently, Corzana et al 33 using combined NMR experiments with molecular dynamics simulation found that glycosylated threonine residues are quite rigid in solution. The authors established that the PPII helix, together with the rigidity of the threonine-containing glycopeptides, make this system unique to structure the water molecules of its first hydration shell.…”
Section: New Mechanism Of Antifreeze Actionmentioning
confidence: 99%
“…The uniqueness of the PPII conformation of AFGPs is that it allows all backbone groups to be positioned on the same side of the molecule facing in close proximity the disaccharide group, while the relatively hydrophobic Ala groups occupy the primary position on the opposite side. 31,33 The disaccharide group at such position adds stability and interconnectivity in the extended water structure created by the peptide backbone of the PPII helix. This arrangement is crucial since the use of a glycosylated serine residue in place of threonine, which has a side-chain hydroxyl group but no methyl group, was unable to confer thermal hysteresis.…”
Section: New Mechanism Of Antifreeze Actionmentioning
confidence: 99%